Teacher`s Understanding Of Psychological And Developmental Principles In Effective Istruction - Ummi Masrufah Maulidiyah; Kartika Az Zahrah; Nurul Izah; Rahma Nur Nuzula; Rivuatul Hasanah (P3I UMSurabaya, 2025)
A teacher's deep understanding of psychological and developmental principles constitutes the essential foundation for effective instruction. This abstract discusses the critical importance of this knowledge in supporting student learning success. Psychological understanding encompasses cognitive mechanisms (such as cognitive load and memory) and motivational factors (e.g., Self-Determination Theory), enabling teachers to design learning environments and strategies that intrinsically foster student engagement. Meanwhile, developmental understanding ensures that instructional materials and expectations align with students' cognitive and socio-emotional maturity stages (Developmentally Appropriate Practice). The integration of these two knowledge bases, often termed Pedagogical-Psychological Teaching Knowledge (PPTK), allows teachers to make sound decisions, manage the classroom effectively, and implement differentiation. This study uses a literature review method, which involves examining various written sources such as books, journals, and academic reports, rather than collecting data directly from the field.